2014
DOI: 10.1038/bjc.2014.444
|View full text |Cite
|
Sign up to set email alerts
|

Predicting response and survival in chemotherapy-treated triple-negative breast cancer

Abstract: Background:In this study, we evaluated the ability of gene expression profiles to predict chemotherapy response and survival in triple-negative breast cancer (TNBC).Methods:Gene expression and clinical–pathological data were evaluated in five independent cohorts, including three randomised clinical trials for a total of 1055 patients with TNBC, basal-like disease (BLBC) or both. Previously defined intrinsic molecular subtype and a proliferation signature were determined and tested. Each signature was tested us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 44 publications
1
80
1
1
Order By: Relevance
“…As proliferation rate is known to be associated with chemotherapy response (32), it was critical to confirm that the resistance mediated by JNK knockdown or inhibition was independent of its cytostatic effect. Compared with the effects observed in subconfluent cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As proliferation rate is known to be associated with chemotherapy response (32), it was critical to confirm that the resistance mediated by JNK knockdown or inhibition was independent of its cytostatic effect. Compared with the effects observed in subconfluent cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…29,54 In a clinical research of 1055 patients with TNBC, BLBC or both, only when TNBC can be stratified into BLBC subtype could patients be identified with notably better response after chemotherapy. 55 Previous studies show that BLBC harbors the hallmarks of BRCAness. 21 In conclusion, BLBC is an important consideration for prediction of platinum efficacy in TNBC.…”
Section: Molecular Subtype Associated Biomarkersmentioning
confidence: 99%
“…In practice, Luminal A tumors have lower ROR scores than other subtypes. Previous studies have shown that the sensitivity of a tumor to chemotherapeutic agents is associated with its proliferative state (22)(23)(24). Thus, it is not surprising that ROR score, as an inclusive measure of a tumor's proliferative potential, can predict those tumors that would be more sensitive to chemotherapeutic agents.…”
Section: /Her2mentioning
confidence: 99%